The reality of using the Internet in the learning process among a sample of students from College of Imam Al-Adam (may Allah have mercy on him) University (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to investigate the reality of using the Internet in the learning process from the viewpoint of the students of the College of Al-Imam Al-Adam University in Iraq. The research has used the descriptive approach, and the study sample consisted of (738) students from the college departments at all levels. An electronic questionnaire was applied to them consisting of (4) items. Thus, the study was applied in the second semester of the academic year (2019/2020). By analyzing the collected data after submitting, it was found that the most percentage of students who use the Internet are from the Department of Jurisprudence while the most used site in the learning process is (Google). The number of hours that the majority of students spend on the Internet is between (1-4) hours per day. Most of the reasons and obstacles that faced the students is the weakness of the Internet. The study presented some recommendations and suggestions.